2021
DOI: 10.1007/s00392-021-01857-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic comparison in takotsubo syndrome: novel insights from the International Takotsubo Registry

Abstract: Background Ethnic disparities have been reported in cardiovascular disease. However, ethnic disparities in takotsubo syndrome (TTS) remain elusive. This study assessed differences in clinical characteristics between Japanese and European TTS patients and determined the impact of ethnicity on in-hospital outcomes. Methods TTS patients in Japan were enrolled from 10 hospitals and TTS patients in Europe were enrolled from 32 hospitals participating in the Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…complications [18]. Moreover, a study that examined ethnic disparities in TCM using data from the International Takotsubo Registry found that Japanese patients had higher in-hospital mortality and required more interventions, such as vasopressor or IABP use [19] This is consistent with our findings that Asian or Pacific Islander patients experienced higher mortality rates. With the limited data and analyses on the ethnic disparities that exist in TCM patients, further studies are needed to examine the reasons behind higher mortality rates in certain races compared to others.…”
Section: Discussionsupporting
confidence: 90%
“…complications [18]. Moreover, a study that examined ethnic disparities in TCM using data from the International Takotsubo Registry found that Japanese patients had higher in-hospital mortality and required more interventions, such as vasopressor or IABP use [19] This is consistent with our findings that Asian or Pacific Islander patients experienced higher mortality rates. With the limited data and analyses on the ethnic disparities that exist in TCM patients, further studies are needed to examine the reasons behind higher mortality rates in certain races compared to others.…”
Section: Discussionsupporting
confidence: 90%
“… 13 , 30 In terms of in-hospital complications, Black patients presented with higher rates of cerebrovascular accident, acute kidney injury, and inpatient mortality and had longer hospital stays than their White counterparts, 18 , 21 suggesting that race may play a role in the outcomes of Black patients with TTS; this finding is in contrast with those of previous studies. 18 , 19 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that ethnicity itself does not influence the prognosis for TTS patients. The poorer in-hospital outcomes among Japanese patients are primarily attributed to the higher incidence of physical triggers ( 15 ). African-American TTS patients have been reported to have more frequent in-hospital complications, such as respiratory failure and stroke and require mechanical ventilation, as compared with Caucasians and Hispanics ( 16 ).…”
Section: Discussionmentioning
confidence: 99%